2021
DOI: 10.1108/itp-05-2020-0298
|View full text |Cite
|
Sign up to set email alerts
|

Technology intervention for preventing COVID-19 outbreak

Abstract: PurposeThe purpose for writing this article is derived from the misery and chaos prevalent in the world due to the coronavirus pandemic – since late 2019 and still continuing as of December 2020.Design/methodology/approachA blockchain-based solution to verify the country visit trail and disease and treatment history of the passengers who arrive at the immigration counters located at various national borders and entry points is proposed. A fuzzy inference based suspect identifier system is also presented in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…COVID-19 has been spreading globally via immigration inspections at airports, seaports, riverports, and land ports [9]. As such, airports and airlines are implementing various countermeasures to prevent the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has been spreading globally via immigration inspections at airports, seaports, riverports, and land ports [9]. As such, airports and airlines are implementing various countermeasures to prevent the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…However, one can argue that COVID‐19 has become more infectious and evolved as a global pandemic; its influence on business operations became unforeseeable. Later, International Labor Organization ( 2020 ) suggested that the pandemic has affected around 232 million wholesale and retail trade, providing 70% of the global employment (Pandey & Litoriya, 2021 ). Therefore, the COVID‐19 pandemic, which is viewed initially as a WSE, turned out to be BSE, as firms were unable to assess the impact of COVID‐19 on their operations.…”
Section: Background Workmentioning
confidence: 99%